Application of nitrogen sufficiency conversion strategy for microalgae-based ammonium-rich wastewater treatment. Issue 20 (17th October 2016) - Wang, Jinghan; Zhou, Wenguang; Yang, Haizhen; Ruan, Roger
ABSTRACT: Ammonium ( -N)-rich wastewater, a main cause for eutrophication, can serve as a promising medium for fast microalgae cultivation with efficient -N removal. To achieve this goal, a well-controlled three-stage treatment process was developed. Two trophic modes (mixotrophy and heterotrophy) in Stage 1 and Stage 2, with two nitrogen availability conditions (N sufficient and N deprived) in Stage 2, and different -N concentrations in Stage 3 were compared to investigate the effects of nitrogen sufficiency conversion on indigenous strain UMN266 for -N removal. Results showed that mixotrophic cultures in the first two stages with N deprivation in Stage 2 was the optimum treatment strategy, and higher -N concentration in Stage 3 facilitated both microalgal growth and -N removal, with average and maximum biomass productivity of 55.3 and 161.0 mg L −1 d −1, and corresponding removal rates of 4.2 and 15.0 mg L −1 d −1, respectively, superior to previously published results. Observations of intracellular compositions confirmed the optimum treatment strategy, discovering excellent starch accumulating property of strain UMN266 as well. Combination of bioethanol production with the proposed three-stage process using various real wastewater streams at corresponding stages was suggested for future application.